IMPLEMENTATION OF CORUPTION CRIMINAL SANCTIONS AGAINTS COUNTRY OFFICERS WHO CONDUCTED CRIMINAL ACT OF CORUPTION DURING COVID 19 - Mulyadi, Mulyadi; Pakpahan, Elvira Fitriyani (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
Corruption has caused damage to various lives of the people, nation, and country. Pandemic Covid 19 is currently increasingly infecting the Indonesian economy. Corruption is one of the causes of the nation's economic system to decline very rapidly. The purpose of this study is to determine the implementation of criminal sanctions against corruption against unscrupulous state officials who commit criminal acts of corruption during the Covid 19 pandemic. The method used in this study is the Normative Juridical Method. The Corruption Eradication Commission (KPK) will provide stricter penalties for those who commit criminal acts of corruption committed in the midst of the corona covid-19 pandemic. Disaster management is an activity or effort carried out in the context of prevention, mitigation, emergency response and recovery related to disasters carried out before and after a disaster.